Long-term low carbon strategy of Morocco: A review of future scenarios and energy measures - El Hafdaoui, Hamza; Khallaayoun, Ahmed; Ouazzani, Kamar (Results in engineering, 2024)
This comprehensive review article illuminates Morocco's proactive response to climate change challenges over the past decades. Faced with drought episodes akin to other Mediterranean countries, Morocco contends with significant water stress, boasting limited water resources estimated at 20 billion cubic meters and an annual per capita consumption of 700 m3. The country experiences a temperature surge of 0.3–2.5 °C, coupled with decreased precipitation, heightening the impact of climate change on water resources. Morocco plans a 40 % reduction in emissions by 2030 (18.3 % unconditional, 27.2 % conditional on international aid) and an impressive 77 % decrease in emissions by 2050 compared to Business as Usual levels. The study offers a comprehensive, groundbreaking analysis, representing the first comprehensive review of Morocco's low-carbon strategy and energy initiatives. It meticulously examines 155 research papers through the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, categorizing solutions into engineering and managerial domains. Covering power, transport, building, industry, and agriculture, the article provides a taxonomy of engineering solutions, including renewable energy, energy auditing, efficiency, sufficiency, and digitalization of management. Simultaneously, managerial solutions, ranging from education to subsidies and policy reforms, are detailed. These solutions contribute to Morocco's standing as a leader in climate action and clean energy transition. Despite these significant contributions, the article acknowledges potential limitations, including reliance on available literature and regional variations in solution applicability. Nonetheless, it serves as a foundational resource for understanding Morocco's endeavors in addressing climate change and promoting sustainable energy practices. •Morocco addresses water stress and temperature increase due to climate change.•Morocco targets 40 % emission reduction by 2030 and 77 % by 2050.•The paper systematically synthesizes 155 research papers using the PRISMA methodology.•The study reviews the energy use and emissions of various sectors in Morocco.•The paper is a foundational resource for understanding Morocco's climate efforts.